Demotic ostraca and their use in Egyptian temple context from the Greco-Roman period: Soknopaiou Nesos and Hut-Repit - Lippert, S; Schentuleit, M (De Gruyter, 2020)
The focus of this article lies on the ostraca from the temple complexes of Soknopaiou Nesos in the Fayum and Hut-Repit in Middle Egypt written in Demotic, a cursive writing system used from the seventh century BCE to the fifth century CE. The two roughly contemporary sets of ostraca provide the opportunity to compare the use of Demotic ostraca for different text forms and text types and the role of potsherds versus other writing materials in the administrative, economic, and cultic life of Egyptian provincial temples in the late Ptolemaic to early Roman period.